2005
DOI: 10.1590/s0100-67622005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Influência da idade e da posição ao longo do tronco na composição química da madeira de Eucalyptus grandis Hill ex. Maiden

Abstract: RESUMO -Este trabalho estudou a variação da composição química na madeira de Eucalyptus grandis de quatro diferentes idades (10, 14, 20 e 25 anos), proveniente de talhões comerciais. As amostras foram coletadas de três discos, retirados da base e das extremidades das duas primeiras toras, de 3 m cada uma, de 16 árvores (quatro para cada idade), totalizando 48 discos. Os valores médios dos teores de holocelulose, lignina e extrativos foram de 69, 27 e 4%, respectivamente. Verificou-se que os teores de extrativo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
4
28

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 1 publication
1
6
4
28
Order By: Relevance
“…This increase is likely related to the higher concentration of low molecular weight carbohydrates in taller parts of the trunk, closer to the apical meristem. This data agree with values found in literature, as for instance results described by Silva et al (2005).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This increase is likely related to the higher concentration of low molecular weight carbohydrates in taller parts of the trunk, closer to the apical meristem. This data agree with values found in literature, as for instance results described by Silva et al (2005).…”
Section: Resultssupporting
confidence: 93%
“…This increase is likely related to higher sugar quantities in taller parts of the trunk, closer to the apical meristem. Silva et al (2005) investigated the infl uence of age and position relative to the trunk on the chemical composition of wood from Eucalyptus grandis Hill ex. Maiden and found that older, lower log sections had higher extractives and lignin contents than remaining log sections, corresponding to maturer wood, and they also found that younger, higher log sections had higher holocellulose contents.…”
Section: Resultsmentioning
confidence: 99%
“…Quilhó et al (2006) concluíram que as dimensões das fibras em clones de E. grandis × E. urophylla não apresentaram tendência definida de variação no sentido medulacasca. Silva et al (2007) observaram um aumento no comprimento das fibras no sentido medula-casca para E. grandis e a mesma tendência foi verificada para E. dunnii por Florsheim et al (2009 Lima IL, Longui EL, Garcia R, Luca EF, Silva Júnior FG, Florsheim SMB Floresta e Ambiente 2011;18(3):289-298 296 do teor de extrativos que apresentou aumento significativo, no sentido medula-casca, enquanto que os teores de lignina e holocelulose não mostraram variação significativa.…”
Section: Methodsunclassified
“…O efeito da idade sobre algumas características da madeira é bastante claro, como no caso do teor de cinza, que diminui com a idade da árvore (KUMAR et al, 2009;MORAIS, 2008;TRUGILHO et al, 1996), e a densidade básica aumenta com a idade da árvore (KUMAR et al, 2010(KUMAR et al, , 2011LEMENIH;BEKELE, 2004;MORAIS, 2008;RAYMOND, 2000;SILVA, 2011;SILVA et al, 2005;STURION et al, 1988;TRUGILHO et al, 1996;VITAL, 1984).…”
Section: Introductionunclassified